APLIKASI MINIMUM SPANNING TREE ALGORITMA PRIM DAN KRUSKAL PENENTUAN LOKASI PEMBANGUNAN JALAN BARU - Minarwati (LPPM STMIK El Rahma Yogyakarta, 2021)
Network analysis can describe a network that must be run in a certain order and is limited by time, one of which is to complete a project. PERT / CPM is a method in network analysis that can be used to solve problems in a work project. Graph is a chapter / discussion in Discrete Mathematics. Graph is a collection of vertices and edges. In the discussion of graph, there is a discussion about trees, it is a graph that is undirected and does not contain circuits. In a tree, it can be determined that the minimum spanning tree / minimum spanning tree is a sub or part of the Graph in the form of a tree and has the same number of nodes as the initial Graph. The road construction project is one of the projects that is suitable for analysis using the spanning tree application in order to obtain the optimal road construction route with the shortest distance between locations. And using PERT / CPM network analysis to get the right order of work so that the work can be completed appropriately both the time used and the costs incurred